Uma estratégia para tratar os aspectos sócio-culturais no desenvolvimento distribuído de software - Soares, Paulo Henrique (2011)
The growing computerization of nowadays society also increased the number of enterprises in service sector, which develops software and automatized solutions to industrial and commercial sectors. The growing demand made difficult to find qualified I. T. professionals, considering that there is a great demand to hire their work force. The solution found by the great corporations is D.S.D (distributed software development) which consists in fractionating software creation process to professionals residents all over the world, all of them working on the development of the same projects. By doing so, it is possible to hire skilled workers everywhere in the world at relatively low wages (costs). However, task distribuition generates some problems - that does no exist when software is deveolped by a colocated team - such as: difficulty on language and communication, conflict of time zones, lack of team-mate spirit, lack of confidence in each other - specially between those who are in remote places - and also and principally problems generated by socio-cultural aspects, which will be the nuclear theme of this research. This article will work on strategies which aims to provide support for chairman and managers of software businesses, easing to solve troubles caused by the social singularities between workers from different places.